Analisis Keterlaksanaan Dan Aktivitas Belajar Peserta Didik Menggunakan Model Pembelajaran Inquiry Cycle Berbantuan Javalab - Mashita, Hety; Martini, Martini; Mahdiannur, Muhamad Arif (Pendidikan Fisika UIN Alauddin Makassar, 2024)
This study aimed to understand the implementation and learning activities of students after the implementation of the inquiry cycle learning model assisted by JavaLab. This research used an observational research design by involving 32 students 7th grade. Data collection technique used Stallings snapshot observation. Then, data were analyzed using the results of learning implementation and the percentage of learning activities. Based on the results of data analysis, it showed that the implementation of learning with the inquiry cycle learning model assisted by JavaLab was carried out in all phases and obtained a percentage of learning activities with more dominant active instructions. Students actively participate in the learning process through discussions, practice or drills, and assignments. Based on this explanation, although there are limitations, it can be concluded that the application of the inquiry cycle learning model assisted by JavaLab has a good impact on student learning activities in the implementation of learning.